Short Communication: Fusarium as endophyte of some terrestrial orchid from Papua, Indonesia - SUPENI SUFAATI; VERENA AGUSTINI; SUHARNO SUHARNO (Society for Indonesian Biodiversity, 2016)
Sufaati S, Agustini V, Suharno. 2016. Fusarium as endophyte of some terrestrial orchid from Papua, Indonesia. BiodiversitasÂ 17: xxx. The aim of the study was to identify endophytic fungi associated with the roots of terrestrial orchid Phaius tankervilleae (Banks)Â Blume, Dendrobium lancifolium A. Rich var. papuanum and Calanthe triplicata (Willem) Ames from Papua, Indonesia. The endophytic fungi were isolated from the transversal section of the orchid roots. Identification of the endophytes was carried out based on the morphological characters. The phylogenetic analysis of nucleotide sequences generated from ITS rDNA region of the endophytic fungi isolated from P. tankervilleae showed that those isolates were determined as Fusarium solani. This is the first report of F. solanifound as endophyte of P. tankervilleae in Papua. While the ITS rDNA of Fusarium isolated from C. triplicata need to be sequenced for further identification.